ANALISIS KESALAHAN LEKSIKAL DAN SINTAKSIS DALAM MENULIS TEKS EKSPOSISI PADA SISWA KELAS X - Hayatun Rahmi; S Nofiana; Muhammad Iqbal (Jurnal Dedikasi Pendidikan, 2023)
This study aims to obtain an overview of the lexical and syntactic errors made by class X students of SMA Negeri 1 Bandar Baru Pidie Jaya in writing exposition texts. The method used in this research is descriptive analysis method. The population in this study were all students of class X SMA Negeri 1 Bandar Baru Pidie Jaya, totaling 272 students and who would be determined as the sample in this study amounted to 41 students. The data collection technique used in this study is a test analysis technique in the form of interviews and documentation. Meanwhile, the data analysis technique used in this research is essay which is read data, errors are identified, errors are described, errors are classified, and then the error percentage is calculated. The results of this study indicate that the level of lexical and syntactic errors in class X students of SMA Negeri 1 Bandar Baru is 3.69% for lexical errors and 42.39% for syntactic errors. Therefore, it can be said that class X students of SMA Negeri 1 Bandar Baru can already write expository essays well. This can be said to be good based on the results of research in which there are very low category of lexical errors and low category of syntactic errorsÂ